Microbiology of the white coat in a dental operatory - M Malini; Titus K Thomas; Darpan Bhargava; Smiline Girija (Wolters Kluwer Medknow Publications, 2012)
Background: It remains important to have a thorough knowledge of the micro-flora harboring the white coats of doctors to minimize cross-contamination and improve patient safety by reducing the risk of nosocomial infections. This study presents the microbiological analysis of the white coats in clinical departments of a dental college and hospital. Materials and Methods: The swabs for the study were taken from the white coats of undergraduate students posted in various clinical departments, interns, and the post-graduate students. The microbial contamination was studied by observing and recording the colony morphology on the culture plates, Gram's staining with light microscopic screening of the slides, and the biochemical characterization of the isolates using standard microbiology protocols. Results: Microbiological analysis of swabs taken from the white coats in the dental operatory showed that 100% coats had bacterial contamination. Out of 30 swabs collected, 46 cultures were obtained. 50% cultures showed Gram-positive cocci, making it the major microbial group contaminating the white coats in the dental operatory. Conclusion: The presented study highlights the fact that the white coats are a potential source of cross infection. The results of this study mandate a strict audit process and protocols to be set in place for preventing cross-contamination from the white coats in a dental operatory.